(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article contains information about the life and work of the poet Andalib, who lived and worked in the 19th century, as well as his famous work “Shahnomai Andalib”. The article also describes the reasons for writing the work, its components, and the experiences of the period.